Lesões podais em ovinos na mesorregião sudoeste rio-grandense - Silveira, Caroline da Silva (2016)
Foot diseases are one of the main disorders in small ruminant flocks in several countries and infectious pododermatite (Footrot) is reported as the most frequent podal lesions in sheep in Brazil. In Rio Grande do Sul state, foot diseases still a serious problem for sheep farmers and little has been done to remedy them. Footrot is a notifiable disease and frequent in the region, the official records on the disease situation in herds are scarce. This study aimed to describe the main features of foot lesions observed in sheep from Mesoregion Southwest of Rio Grande do Sul, with emphasis on epidemiology, macroscopic, microscopic and radiographic changes of Footrot injuries. The study was conducted in two steps. Initially, sheep were evaluated on 27 farms, of which 21 showed records of the occurrence of foot lesions in sheep and significant economic losses. Approximately 1,700 sheep, about 10% of the flocks, showed varying degrees of lameness due to foot lesions, macroscopically characterized as mild to severe. Subsequently, they assessed the varying degrees of injuries Footrot in sheep. Hooves with injuries were submitted to macroscopic, radiographic and microscopic evaluation. Thus the disease was classified into five grades of severity ranging from 1 (mild injury) to 5 (severe damage). It has been found that several factors such as weather and handling were favorable for the development of foot injuries and these are associated in most Footrot cases in different stages of evolution. Based on the classification in degrees of infectious pododermatitis it was possible to classify them macroscopically in clinical syndromes proposed as benign and malignant Footrot. This classification facilitates the establishment of control measures with the intention of reduce spread of disease and prevent the development of lesions in affected hooves.